The activity of glyoxylase 1 is regulated by glucose-responsive phosphorylation on Tyr136 - Garcia Cortizo, Fabiola; Pfaff, Daniel; Wirth, Angela; Schlotterer, Andrea; Medert, Rebekka; Morgenstern, Jakob; Weber, Tobias; Hammes, Hans-Peter; Fleming, Thomas; Nawroth, Peter Paul; Freichel, Marc; Teleman, Aurelio A. (Molecular metabolism, 2022)
Objective - Methylglyoxal (MG) is a highly reactive α-oxoaldehyde that glycates proteins. MG has been linked to the development of diabetic complications: MG is the major precursor of advanced glycation end products (AGEs), a risk marker for diabetic complications in humans. Furthermore, flies and fish with elevated MG develop insulin resistance, obesity, and hyperglycemia. MG is detoxified in large part through the glyoxalase system, whose rate-limiting enzyme is glyoxalase I (Glo1). Hence, we aimed to study how Glo1 activity is regulated. - Methods - We studied the regulation and effect of post-translational modifications of Glo1 in tissue culture and in mouse models of diabetes. - Results - We show that Glo1 activity is promoted by phosphorylation on Tyrosine 136 via multiple kinases. We find that Glo1 Y136 phosphorylation responds in a bimodal fashion to glucose levels, increasing in cell culture from 0 mM to 5 mM (physiological) glucose, and then decreasing at higher glucose concentrations, both in cell culture and in mouse models of hyperglycemia. - Conclusions - These data, together with published findings that elevated MG leads to hyperglycemia, suggest the existence of a deleterious positive feedback loop whereby hyperglycemia leads to reduced Glo1 activity, contributing to elevated MG levels, which in turn promote hyperglycemia. Hence, perturbations elevating either glucose or MG have the potential to start an auto-amplifying feedback loop contributing to diabetic complications.